(untitled) (American Journal of Pedagogical and Educational Research, 2026)
The study explores the application of technology in the pedagogical process of secondary school History, which is premised on the fact that technology has the ability to concretize knowledge of history when employed in the pedagogical process in history amongst students, especially those at the secondary school level of education. The study made use of secondary data for its exploration of the application of technology in the teaching and learning process, and on the strength of that, the study concludes that the benefits of technology usage in education and history in particular cannot be overemphasized as it makes for seamless teaching and transfer of from the instructor to the learners with regards to historical facts on cultural legacy, political growth, and societal development. The study suggested that the relevant authorities in the education sector like the government, civil societies and philanthropist should assist with the supply of technology and relevant historical data that will assist in the pedagogical process of history amongst learners.